Promoting the Brand Inside: The Conceptualization of Nonprofit Internal Branding and Its Relationship With Employees’ Brand Performance - Zhang, Ran; Wu, Yunqiao; Ye, Chao (Frontiers in Psychology, 2022)
As a value-led entity, the nonprofit depends on its staff for the delivery of the brand value outsides and thus promoting the brand inside is crucial to the development of the nonprofits. Using a sample of 290 full-time staff working in 270 nonprofits in China, two related studies were conducted. Study 1 aimed to develop and validate a new scale for internal branding in the nonprofit context, whilst Study 2 aimed to investigate the linking mechanism between internal branding and brand performance with the mediating roles (including chain mediation) of the person–organization fit (POF) and intent to stay with the brand (IntSB). As predicted, the results revealed that: (1) the nonprofit internal branding (NIB) scale is a three-dimensional construct that is composed of brand-centered training, internal brand communication, and brand-oriented leadership, (2) internal branding positively predicts POF, IntSB, and brand performance, and (3) POF and IntSB sequentially mediate the internal branding–brand performance relationship. The implications of our findings for internal branding in the nonprofit context are discussed.